Analisis Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan (Studi Kasus di KSPPS BMT As Salam Cabang Sarimulyo) - Siska Norsafera; Hendrajaya Hendrajaya (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyse the implementation of human resource development and its impact on employee performance at KSPPS BMT As Salam Sarimulyo Branch. The study focuses on the execution of training, education, and development programs, the assessment of employee performance across the dimensions of work quality, work quantity, discipline, teamwork, and responsibility, as well as the role of human resource development in enhancing individual and organisational performance. To address these issues, the study applies human resource development theory and employee performance theory. Data were collected through in-depth interviews, direct observation, and organisational documentation, and analysed qualitatively using the Miles and Huberman interactive analysis model. The findings indicate that human resource development programs have been implemented in a structured and continuous manner, improving technical competencies, understanding of Sharia principles, professionalism, discipline, teamwork, and employee responsibility. The study also reveals that the contextual integration of training, education, and development within a Sharia microfinance institution forms a pattern of performance improvement that is not only technical in nature but also grounded in values and work ethics. Challenges such as limited training time and variations in employee participation can be minimised through adaptive adjustments in scheduling, content, and career development strategies. Therefore, this study emphasises that human resource development not only contributes to improving employee performance but also strengthens the conceptual framework linking human resource development and performance within the context of Sharia microfinance institutions, thereby offering both theoretical and practical contributions to value-based human resource management.